Improved physical and osteoinductive properties of demineralized bone matrix by gelatin methacryloyl formulation. (8th February 2020) - Ramis, Joana M.; Blasco‐Ferrer, Marc; Calvo, Javier; Villa, Oscar; Cladera, Margalida M.; Corbillo, Cristina; Gayà, Antoni; Monjo, Marta
Abstract: The demineralized bone matrix (DBM) is the most widely used bone allograft, which is obtained by removing the mineral component of bone, leading to exposure of the proteins responsible for osteoinduction. For clinical use, DBM shall be formulated with a carrier that provides consistency and improves its osteoinduction. In this study, three DBM formulations with glycerol (Gly), hyaluronic acid (HA), and gelatin methacryloyl (GelMA) were evaluated measuring their physicochemical properties (microstructure, compressive strength, and serum cohesivity) and their osteoinductive capacity both in vitro using C2C12 cells and umbilical cord human mesenchymal stem cells and in vivo in an ectopic bone formation model in athymic mice. To assess the effectiveness of DBM in vitro in inducing the differentiation into osteoblasts, alkaline phosphatase (ALP) activity was assessed in combination with a cytotoxicity assay. In vivo, new bone formation was assessed by histological and radiological analysis. In the compression and in the serum cohesive assays, the GelMA DBM formulation showed its superiority over the other formulations. In addition, GelMA showed a more compact structure analysed by scanning electron microscopy. Higher cell toxicity was observed on Gly formulations in vitro, whereas GelMa and HA showed very low toxicity. All formulations significantly improved ALP activity compared with control. In the in vivo studies, GelMA showed the greatest osteoinductive potential with a higher percentage of new bone and bone marrow formation. Our results suggest GelMA is useful as a carrier for DBM designed to promote the formation of the new bone.